2011
DOI: 10.1016/j.pupt.2010.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Association of ex vivo vascular and bronchial dysfunctions in smokers

Abstract: Word count: 204Background. It has recently been shown that systemic endothelial dysfunction is associated with airflow limitation in COPD. We conducted this ex vivo study to assess whether endothelial dysfunction of pulmonary arteries of former smokers was associated with modifications of airway functions. Conclusion. Endothelial dysfunction of pulmonary arteries is associated with increasedresting tone and impaired cGMP-mediated dilation of airways in former smokers, suggesting common underlying mechanisms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Increased arginase activity has also been associated with airway hyperresponsiveness [33,34]; we previously demonstrated that increased arginase activity is involved in airway sensitivity in smokers [35]. Overall, elevated arginase activity may be one of the mechanisms underlying both pulmonary arterial dysfunction and bronchial dysfunction [36]. Studies with L-arg supplementation have shown inconsistent effects on both systemic and pulmonary endothelial functions [37][38][39].…”
Section: Discussionmentioning
confidence: 98%
“…Increased arginase activity has also been associated with airway hyperresponsiveness [33,34]; we previously demonstrated that increased arginase activity is involved in airway sensitivity in smokers [35]. Overall, elevated arginase activity may be one of the mechanisms underlying both pulmonary arterial dysfunction and bronchial dysfunction [36]. Studies with L-arg supplementation have shown inconsistent effects on both systemic and pulmonary endothelial functions [37][38][39].…”
Section: Discussionmentioning
confidence: 98%
“…Increased arginase activity has also been associated with airway hyperresponsiveness [ 33 , 34 ]; we previously demonstrated that increased arginase activity is involved in airway sensitivity in smokers [ 35 ]. Overall, elevated arginase activity may be one of the mechanisms underlying both pulmonary arterial dysfunction and bronchial dysfunction [ 36 ].…”
Section: Discussionmentioning
confidence: 99%